A weighted aggregation and closeness approach to measuring the compactness of landscape with multiple parts'. (May 2016) - Zhou, Jinhao; Xiao, Ningchuan; Liu, Lin; Li, Qiuping
Highlights: We developed a new compactness measure for disconnected landscape patterns. We designed three experiments to validate the effectiveness of the new measure. We compared the new measure with other compactness measures systematically. We took closeness into consideration to improve traditional compactness measures. We standardized the range of the measure value to [0, 1] for various applications. Abstract: Existing landscape ecology measures may not effectively capture the compactness of patterns that have multiple, disconnected parts. We develop a new way of measuring the compactness of such disconnected landscape patterns. Our method uses a map generalization approach to aggregating the multiple parts into a connected polygon while preserving the overall shape of the original pattern. We then measure the compactness by considering the weighted area-perimeter ratio of the aggregated shape and the closeness between the parts. Our measure, called weighted aggregation and closeness ( WAC ), is compared with 15 other landscape ecology metrics and the results suggest that WAC outperforms the other metrics by providing a more reasonable description of the compactness for patterns with multiple parts.